Energy management system requirements according to International Standards lSO-50001:2018: A case study in the General Electricity Distribution Company (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The research aims to evaluate the availability of requirements 50001:2018 and the extent of its impact on achieving the strategy for using energy management systems and its great importance in improving energy-related performance and providing the scientific method for establishing and operating operations and activities aimed at rationalizing energy and environmental reality and through carrying out organized procedures for application in the company. The research study dealt with evaluating the availability of energy management systems requirements in accordance with ISO requirements (50001:2018) and the actual reality in the Ministry of Electricity / General Company for Baghdad Electricity Distribution. The study was able to identify the problem and suggested a mechanism and procedures according to appropriate steps that would enable the surveyed company to address the gaps and implement the requirements of the standard. The research relied on a case study approach to the studied phenomenon( Case study) Because it helps to collect data through the method of observation, personal interviews, field experience, and interviewing officials, as well as using (Checklists), the paragraphs of which were prepared based on the requirements of this standard, and the researcher used statistical analysis methods represented by the arithmetic mean and percentage of application and documentation in a way that helps in comprehensive and realistic analysis.The study reached a set of results, including that the company has a weakness in the level of application and documentation of the requirements of the standard and the actual reality.The most prominent recommendations of the study were to provide a mechanism for the necessity of commitment and adoption by senior management to implement the energy management system, in which the main steps are clarified in accordance with the procedures and regulatory matters followed, and to develop a systematic mechanism to identify risks and how to address them and reduce their negative effects for application in the company